Assessing and evaluating student contribution to electronic discussions - Herrmann, A.; Downie, Jill; O'Connell, B. (Southern Cross University, 2001)
Tutors in face-to-face teaching and learning contexts, evaluate students' participation in order to provide assessment that contributes towards the students' final grade. Similarly, in on-line learning environments, there is a perceived need to reward the quantity and quality of student interactivity. However, the different nature of the context presents new challenges. Specifically, without the visual cues and immediate feedback, so important in face-to-face communication, the evaluation of students' contributions to on-line learning activities and interaction demands new instructional and assessment skills. A unit of study at an Australian university, using computer mediated communication, was reviewed to address questions related to the appropriateness of an on-line evaluative process.